PRODUKSI BIOGAS DARI RUMPUT LAUT Sargassum sp. - Jai Murjani; R. Marwita Sari Putri; Yulia Oktavia; Aidil Fadli Ilhamdy (Marinade, 2020)
Biogas production is done using the raw material of Sargassum Sp. Based on the results of the characteristic testing obtained the protein value of 11.23%, fat content 0.86%, water content 13.93%, ash content of 13.74%, and C/N ratio of 51.96%. Biogas production is divided into 2 phases namely batch method 1:1, 1:2, and Method Digester 1:1, 1:2. The COD value calculation is done before the biogas production process to determine the amount of oxygen needed to oxidize organic substances, which is 640,785.6 ml/L. The test results of CH4 methane gas and CO2 carbon dioxide in the 1:1 treatment are CH4 177525.17 ppm, CO2 124651.0033 ppm, and 1:2 CH4 300338.46 ppm, CO2 247525.3367 ppm. The value of pH measurements during the biogas production process 1:1 is 6-7 with a temperature value of 28-40 oC 1:2 which is 6-7 and the temperature value is 27-32oC